The Effect of Work Motivation on Employee Performance (Empirical Study of CV. Ayna Factory Sumedang and CV. Seven Brave Sumedang) - Ratnasari, Shofia Annisa; Aini, Alifah Nur; Windiani, Elis (Journal of Bussines Management Basic, 2024)
This study entitled the effect of work motivation on employee performance (empirical study of CV. Ayna Factory Sumedang and CV. Seven Brave Sumedang). The problem of these two companies is the lack of optimization in improving employee performance. This study aims to determine the effect of work motivation on employee performance at CV. Ayna Factory Sumedang and the effect of work motivation on employee performance at CV. Seven Brave Sumedang. This study uses quantitative methods with a survey approach, documentation, data collection techniques, namely by observation and questionnaires. Sampling was carried out by saturated sampling with a total of 54 respondents from CV. Ayna Factory Sumedang and 44 respondents from CV. Seven Brave Sumedang. The data analysis technique uses simple linear regression analysis, correlation test, correlation coefficient, determination coefficient and t test with data processing using the Statistical Product and Service Solution (SPSS) version 25. The results of the discussion of the coefficient of determination test (R Square) show that the effect of work motivation on employee performance at CV. Ayna Factory Sumedang of 67.9% and the influence of work motivation on employee performance at CV. Seven Brave Sumedang is 23.7%, and the rest is influenced by other factors such as leadership, awards, structure, job design, resources, work environment, and others that are not discussed in this study. The results of the t test show that work motivation has a positive and significant effect on employee performance at CV. Ayna Factory Sumedang. And also work motivation has a positive and significant effect on employee performance at CV. Seven Brave Sumedang